Palliative sedation – a snapshot of current practice. Issue Volume 2:Issue (2012)Supplement 1 (1st March 2012) - Harrison, Tim; Robertshaw, Carolyn
Abstract : Background: The use of sedatives in palliative care is under increasing scrutiny. Many different drugs are used and, although midazolam is often the preferred choice, there is no established consensus as to best practice. At a recent course on symptom control delegates were asked a series of questions in order to provide a snapshot of current practice. Aims: To ascertain preferred choices of drugs used in sedation in order to facilitate development of a 'sedation ladder' to guide practice. When midazolam is used as first choice sedative, to establish at what dose addition of a second agent is considered. Method: 250 delegates were presented with a list of nine choices of drug that may be used for palliative sedation. Using an electronic feedback system they were asked to indicate their usual first, second and third choice. In the scenario of midazolam being used as first choice sedative they were also asked 'What dose (of midazolam) do you consider adding a second agent?' Results: The 250 delegates included 127 doctors, 115 specialist nurses and 3 pharmacists. Midazolam was the first choice sedative for 81% of the delegates responding. Levomepromazine was the second choice sedative for 82%. Third choice sedative was more evenly balanced between haloperidol and phenobarbital at 42% and 36.9% respectively. When subcutaneous midazolam is first choice sedative 30% would add an additional drug at 30 mg/24 h whereas 4.8% would not consider this until doses exceeded 100 mg/24 h. Conclusions: Current practice suggests a hierarchy of drug choice in sedation. Midazolam is the most frequent first choice, levomepromazine the second choice and either haloperidol or phenobarbital third choice. This order of preference can be presented as a 'Sedation Ladder' to guide practice.